REGIONAL DIFFERENTIATION IN APPLYING FOR FINANCIAL SUPPORT FROM EU STRUCTURAL FUNDS FOR THE DEVELOPMENT OF AGRICULTURE IN POLAND IN 2004–2006 - Czubak, Wawrzyniec; Kiryluk-Dryjska, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2009)
The objective of paper was to analyze farmer’s interest in the measures of EU structural programs designed for the development of agriculture in Poland in 2004–2006, considering its regional differentiation. Significant regional differentiation in the number of application for measures of structural programs in four analyzed regions has been observed. The highest percentage of holding applied for structural programs measures in the regions already better developed. In particular it concerned the innovative and prospective programs which required more commitment from farmers. Moreover the average value of obtained subvention was higher in better developed agricultural regions. The region where the farmer’s interest in structural programs was the lowest was the south-eastern region of Poland, which (among all analyzed regions) is characterized by the worst agricultural potential.